Lithium secondary battery

By using single-particle and quasi-single-particle positive electrode active materials in lithium secondary batteries, combined with single-wall and bundled carbon nanotube conductive materials, the thermal stability and safety problems of large lithium secondary batteries are solved, and excellent electrochemical performance and safety performance are achieved.

CN119836706APending Publication Date: 2025-04-15LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380063967.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-23
Filing Date
2023-09-22
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing lithium secondary batteries have thermal stability and safety problems when they increase in volume, especially when high voltage fast charging is prone to generate a large amount of heat, causing the battery to catch fire or explode.

Method used

Single particles and/or quasi-single particles are used as the positive electrode active material, and single-walled carbon nanotubes and bundled carbon nanotubes are combined as conductive materials. By adjusting the particle size distribution of the positive electrode active material and the combination of the conductive material, excellent high temperature stability and electrochemical characteristics are formed.

Benefits of technology

Excellent thermal stability and safety in large lithium secondary batteries are achieved, reducing internal heat generation, reducing explosion risk, and improving battery capacity and output characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836706A_ABST
    Figure CN119836706A_ABST
Patent Text Reader

Abstract

The present invention relates to a secondary battery comprising: an electrode assembly in which a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate are wound in one direction; a battery can in which the electrode assembly is accommodated; and a sealing body for sealing the open end of the battery can. The positive electrode plate includes a positive electrode active material layer including a positive electrode active material, a conductive material, and a binder, the positive electrode active material including a lithium nickel-based oxide having at least one of a single particle form or a quasi-single particle form, and the conductive material including single-walled carbon nanotubes and bunchy carbon nanotubes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2022-0121174, filed on September 23, 2022, which is hereby incorporated by reference in its entirety.

[0002] The present invention relates to a lithium secondary battery, and more particularly, to a large-capacity lithium secondary battery capable of achieving excellent thermal stability. Background Art

[0003] With the development of technologies such as electric vehicles and portable electronic devices, the demand for lithium secondary batteries as energy sources is rapidly increasing.

[0004] According to the shape of the battery case, lithium secondary batteries can be divided into can-type batteries (e.g., cylindrical or square batteries) and pouch-type batteries. In these batteries, the can-type battery is manufactured by covering and sealing the top of the battery can with a cover plate after the cake roll type electrode assembly is accommodated in the battery can. The cake roll type electrode assembly is manufactured by sequentially stacking a positive plate, a separator and a negative plate having a sheet shape, and then winding the stack in one direction. A positive electrode connector and a negative electrode connector having a strip shape are respectively provided on the positive plate and the negative plate. The positive electrode connector and the negative electrode connector are connected to the electrode terminal, thereby being electrically connected to an external power source. For reference, the positive terminal is the cover plate, and the negative terminal is the battery can. However, in the can-type battery having the above-mentioned structure according to the related art, the current is concentrated on the electrode connector having a strip shape, so the resistance increases, a large amount of heat is generated, and the current collection efficiency is reduced.

[0005] At the same time, with the recent advancement of vehicle technology, the demand for high-capacity batteries is increasing. Therefore, it is necessary to develop a large can-type battery with a large volume. In the small cylindrical battery (i.e., a cylindrical battery with a form factor of 1865 or 2170) commonly used in the related art, its capacity is small, and therefore, resistance or heat generation does not significantly affect the battery performance. However, when the specifications of the small cylindrical battery in the related art are directly applied to large batteries, there may be serious problems in terms of battery safety.

[0006] As the size of the battery increases, the amount of heat and gas generated inside the battery also increases. The temperature and pressure inside the battery rise due to the heat and gas, and the battery may catch fire or explode. In order to prevent this, the heat and gas inside the battery must be properly discharged to the outside. Therefore, the cross-sectional area of ​​the battery, which serves as a path for discharging heat to the outside of the battery, must increase as the volume increases. However, since the increment in cross-sectional area is generally smaller than the increment in volume, the amount of heat generated inside the battery increases as the battery becomes larger. Therefore, the risk of explosion increases, and the output deteriorates. In addition, when fast charging is performed at high voltage, a large amount of heat is generated around the electrode joint in a short period of time, and the battery may catch fire.

[0007] Therefore, in order to achieve high capacity, it is necessary to develop a can-type battery that exhibits high safety while having a large volume. Summary of the invention

[0008] Technical issues

[0009] In order to solve the above problems, the present invention provides a lithium secondary battery, in which single particles and / or quasi-single particles are applied as positive electrode active materials, and single-walled carbon nanotubes and bundled carbon nanotubes are used together as conductive materials, so that excellent high temperature stability and electrochemical characteristics can be achieved even when the volume of the battery is increased.

[0010] Technical Solution

[0011] According to one example, the present invention provides a lithium secondary battery, which includes: an electrode assembly, in which a positive electrode plate, a negative electrode plate, and a separator inserted between the positive electrode plate and the negative electrode plate are wound in one direction; a battery can, which accommodates the electrode assembly; and a seal, which seals the open end of the battery can, wherein the positive electrode plate includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material, a conductive material and a binder, the positive electrode active material includes a lithium nickel-based oxide having at least one of a single particle or a quasi-single particle, and the conductive material includes single-walled carbon nanotubes and bundled carbon nanotubes.

[0012] Here, the secondary battery may be a cylindrical battery having a shape factor ratio of 0.4 or more, and may be, for example, a 46110 battery cell, a 4875 battery cell, a 48110 battery cell, a 4880 battery cell, or a 4680 battery cell.

[0013] Furthermore, in the secondary battery according to the present invention, each of the positive and negative plates may include an uncoated portion where the active material layer is not formed, and at least a portion of the uncoated portion of the positive or negative plate may define an electrode tab.

[0014] Specifically, the positive electrode plate uncoated portion and the negative electrode plate uncoated portion may be located along the end of one side of the positive electrode plate and the end of one side of the negative electrode plate parallel to the winding direction of the electrode assembly, respectively. A current collector may be coupled to each of the positive electrode plate uncoated portion and the negative electrode plate uncoated portion, and the current collector may be connected to the electrode terminal.

[0015] According to another example, the present invention provides: a battery pack including the lithium secondary battery according to the present invention; and a vehicle including the battery pack.

[0016] Beneficial Effects

[0017] In the lithium secondary battery according to the present invention, single particles and / or quasi-single particles are applied as positive electrode active materials, and therefore, the generation of gas due to the breakage of particles when manufacturing the battery and the generation of internal cracks during charging and discharging can be minimized. Therefore, even in a large battery with an increased volume, excellent safety can be achieved.

[0018] In addition, the lithium secondary battery according to the present invention can use D min The positive electrode active material powder is 1.0 μm or larger, so the thermal stability of the battery can also be improved. When the positive electrode active material powder contains particles with a particle size of less than 1.0 μm, due to the increase in the roller gap pressure in the rolling process, the breakage of the particles may increase and the thermal stability may deteriorate. Therefore, when applied to a large battery, the thermal stability may not be fully guaranteed. Therefore, in the present invention, by using the minimum particle size (D min ) is controlled to be 1.0 μm or larger for the positive electrode active material powder, which can maximize the effect of improving thermal stability.

[0019] Furthermore, in the lithium secondary battery according to the present invention, D 50 , D max The positive electrode active material powder has a properly controlled particle size distribution (PSD). Therefore, the increase in resistance due to the use of a single particle can be minimized, thereby achieving excellent capacity characteristics and output characteristics.

[0020] At the same time, when a positive electrode active material having a single particle and / or a quasi-single particle is used, the distance between the positive electrode active material particles increases compared to the case of using a positive electrode active material having a secondary particle with a bimodal particle size distribution. Therefore, when the bundled carbon nanotubes commonly used in the related art are used as a conductive material, a conductive network is not fully formed between the positive electrode active material particles, so the conductivity is reduced. In addition, with the repetition of charging and discharging, the distance between the positive electrode active material particles is further increased. Therefore, the conductive network is cut off and the life characteristics are deteriorated. By increasing the amount of conductive material to be used, the formation of the conductive network can be increased, but in this case, the viscosity of the positive electrode slurry increases, thereby reducing the coating processability. In order to solve the above problems, the present invention may include a mixture of single-walled carbon nanotubes and bundled carbon nanotubes having a longer average particle size. Therefore, a conductive network between the positive electrode active material particles can be smoothly formed with a relatively small amount of conductive material, and the degradation of the life characteristics can be minimized.

[0021] In addition, in the lithium secondary battery according to the present invention, a silicon-based negative electrode active material having a large capacity may be included as a negative electrode active material. In this case, a higher energy density may be achieved.

[0022] In addition, in the lithium secondary battery according to the present invention, the uncoated portion of the positive plate and the uncoated portion of the negative plate can be used as an electrode joint. In the can-type battery according to the related art, since a large amount of current is concentrated on the electrode joint having a strip shape during charging, a large amount of heat is generated around the electrode joint. In particular, this phenomenon is exacerbated during fast charging, so there is a risk of battery fire or explosion. On the other hand, according to an embodiment of the present invention, when an uncoated portion without an active material layer is formed at each of the ends of the positive plate and the ends of the negative plate and used as an electrode joint, the area through which the current passes increases, and the current concentration is reduced. Therefore, the heat generation inside the battery can be effectively reduced, so that the improvement of the thermal stability of the battery can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a view showing a stacked state before the electrode assembly according to the present invention is wound.

[0024] Figure 2 is a cross-sectional view illustrating a structure of an electrode plate of an electrode assembly according to an embodiment of the present invention.

[0025] Figure 3 is a cross-sectional view showing the structure of a battery according to an embodiment of the present invention.

[0026] Figure 4 is a cross-sectional view showing the structure of a battery according to another embodiment of the present invention.

[0027] Figure 5 is a view for describing the structure of an electrode assembly according to an example of the present invention.

[0028] Figure 6 is a view for describing a battery pack according to an example of the present invention.

[0029] Figure 7 is a view for describing a vehicle including a battery pack according to one example of the present invention.

[0030] Figure 8 This is a measurement image of the cross section of the positive electrode manufactured by Embodiment 1 of the present invention formed by an image management analysis (IMA) system. DETAILED DESCRIPTION

[0031] Hereinafter, the present invention will be described in more detail.

[0032] The terms or words used in this specification and claims should not be restrictively interpreted as ordinary meanings or dictionary-based meanings, but should be interpreted as meanings and concepts that are consistent with the technical spirit of the present invention based on the principle that the inventor can appropriately define the concepts of the terms to best describe and interpret his invention.

[0033] In the present invention, "primary particles" refers to a particle unit having no observable grain boundaries when observed in a field of view at a magnification of 5000 to 20000 times using a scanning electron microscope or electron backscatter diffraction (EBSD). "Average particle size of primary particles" refers to the arithmetic mean value obtained by measuring and calculating the particle size of primary particles observed in a scanning electron microscope image or an EBSD image.

[0034] In the present invention, "secondary particles" are particles formed by the aggregation of multiple primary particles. In the present invention, secondary particles in which no more than 10 primary particles are aggregated are called quasi-single particles to distinguish them from secondary particles formed by the aggregation of tens to hundreds of primary particles in the related art.

[0035] In the present invention, “D min ”, “D 50 ” and “D max " is the value of the particle size in the volume cumulative distribution of the positive electrode active material powder measured by using a laser diffraction method. Specifically, D min is the smallest particle size shown in the volume cumulative distribution, D 50 is the particle size when the volume accumulation is 50%, and D maxIt is the maximum particle size shown in the volume cumulative distribution. For example, the positive electrode active material powder is dispersed in a dispersion medium, and then input into a commercial laser diffraction particle size measuring instrument (e.g., Microtrac MT 3000), and irradiated with ultrasonic waves having a frequency of about 28 kHz and an output of 60 W to obtain a volume cumulative particle size distribution diagram, thereby measuring the value of the particle size in the volume cumulative distribution.

[0036] In the present invention, the "specific surface area" is measured by the BET method, and specifically, can be calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77K) using BELSORP-mino II manufactured by Bell Co., Ltd. of Japan.

[0037] In the present invention, the average particle size of carbon nanotubes means the particle size when the volume accumulation is 50% measured by using a particle size measuring instrument. For example, carbon nanotubes are dispersed in a solvent such as ethanol to prepare a sample, and then the sample is mounted on the particle size measuring instrument. Subsequently, the sample can be irradiated with laser to measure the average particle size of the carbon nanotubes.

[0038] As a result of repeated studies on developing large-scale batteries that have excellent safety and electrochemical characteristics while exhibiting high capacity, the inventors have completed the present invention in the following manner: the inventors found that when a positive electrode active material arranged in the form of a single particle made of one primary particle and / or as a quasi-single particle aggregated of no more than 10 primary particles is used as a positive electrode active material, and single-walled carbon nanotubes and bundled carbon nanotubes are used together as conductive materials, the safety and conductivity and life characteristics of a large-scale battery can are significantly enhanced.

[0039] Specifically, the lithium secondary battery according to the present invention includes: an electrode assembly in which a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate are wound in one direction; a battery can in which the electrode assembly is housed; and a sealing body that seals an open end of the battery can.

[0040] Meanwhile, the positive plate includes a positive active material layer including a positive active material, a conductive material and a binder. The positive active material includes a lithium nickel-based oxide having at least one of a single particle type or a quasi-single particle type, and the conductive material includes single-walled carbon nanotubes and bundled carbon nanotubes.

[0041] Hereinafter, each component of the lithium secondary battery according to the present invention will be described in more detail.

[0042] Electrode assembly

[0043] The electrode assembly is a cake roll type electrode assembly having a structure in which a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate are wound in one direction.

[0044] Figure 1 shows the stacked structure before the electrode assembly according to the present invention is wound, and Figure 2 The cross-sectional structure of the electrode plate (positive electrode plate or negative electrode plate) according to the present invention is shown.

[0045] Reference Figure 1 and Figure 2 The electrode assembly of the present invention can be manufactured by winding the laminate in one direction X, and the laminate is formed by sequentially laminating the separator 12, the positive electrode plate 10, the separator 12, and the negative electrode plate 11 at least once.

[0046] Here, if Figure 2 As shown, each of the positive electrode plate 10 and the negative electrode plate 11 has a structure in which an active material layer 21 is formed on a current collector 20 having a long sheet-like shape, and a partial area of ​​the current collector 20 may have an uncoated portion 22 where the active material layer 21 is not formed.

[0047] As described above, when the positive electrode plate 10 and the negative electrode plate 11 including the uncoated portion 22 are used, a battery having no separate electrode tab and in which at least a portion of the uncoated portion of the positive electrode plate 10 and the negative electrode plate 11 defines an electrode tab (referred to as “tab-less” for convenience) can be obtained.

[0048] For example, the uncoated portion 22 may be formed at an end portion of one side of the current collector 20 and elongated in the winding direction X. A current collecting plate is coupled to each of the positive electrode plate uncoated portion and the negative electrode plate uncoated portion, and the current collecting plate is connected to the electrode terminal. Thus, a battery having a jointless structure can be obtained.

[0049] A battery having a jointless structure can be manufactured by the following method.

[0050] First, the separator, the positive plate, the separator and the negative plate are stacked in sequence so that the uncoated portion 22 of the positive plate 10 and the uncoated portion 22 of the negative plate 11 are located in opposite directions, and then wound in one direction to manufacture a cake roll type electrode assembly. Next, the uncoated portion 22 of the positive plate and the uncoated portion 22 of the negative plate are bent in the direction toward the winding center C, and then the current collector is welded and connected to each of the uncoated portion of the positive plate and the uncoated portion of the negative plate. The current collector is connected to the electrode terminal, and therefore, a battery with a jointless structure can be manufactured. At the same time, the current collector has a larger cross-sectional area than a strip-type electrode joint, and the resistance is inversely proportional to the cross-sectional area of ​​the path through which the current flows. Therefore, when a secondary battery is formed with the above structure, the cell resistance can be significantly reduced.

[0051] Meanwhile, the positive electrode plate uncoated portion and the negative electrode plate uncoated portion may be processed into a plurality of independently bendable segments, and at least a portion of the plurality of segments may be bent toward a winding center C of the electrode assembly.

[0052] The segments may be formed by machining the current collectors of the positive and negative plates through a metal foil cutting process such as laser slotting, ultrasonic cutting, and punching.

[0053] When the uncoated portions of the positive electrode plate and the negative electrode plate are processed into multiple segments, the stress acting on the uncoated portions during bending can be reduced to prevent deformation or damage of the uncoated portions, thereby improving welding characteristics with the current collecting plate.

[0054] The current collector and the uncoated portion are usually joined to each other, for example, by welding, and in order to enhance the welding characteristics, the uncoated portion must be bent as evenly as possible by applying strong pressure to the welding surface of the uncoated portion. However, during this bending process, the shape of the uncoated portion may be irregularly distorted and deformed. The deformed area may contact the electrode of opposite polarity, resulting in micro cracks or internal short circuits in the uncoated portion. However, when the uncoated portion of the positive plate and the uncoated portion of the negative plate are processed into the form of multiple segments that can be bent independently, the stress acting on the uncoated portion during bending can be relieved, thereby minimizing the deformation and damage of the uncoated portion.

[0055] In addition, when the uncoated portion is processed into the form of a segment as described above, a plurality of segments overlap each other during bending, thereby increasing the welding strength with the current collector. When advanced techniques such as laser welding are used, the laser can penetrate the electrode assembly and prevent the problem of melting and evaporation of the separator or active material. Preferably, at least a portion of the plurality of curved segments may overlap at the upper and lower ends of the electrode assembly, and the current collector may be coupled to the plurality of overlapping segments.

[0056] At the same time, Figure 5 As shown, the electrode assembly according to the present invention may have a structure in which an insulating layer 24 is further formed on the positive electrode plate 10. Specifically, the insulating layer 24 may be formed to cover a portion of the positive active material layer 21c and a portion of the uncoated portion in a direction parallel to the winding direction of the electrode assembly.

[0057] In the case of a battery having a jointless structure in which the uncoated portion 22c of the positive electrode plate 10 and the uncoated portion 22a of the negative electrode plate 11 are used as electrode joints, the electrode assembly is formed so that the positive electrode plate 10 can protrude upward from the separator 12 and the negative electrode plate 11 can protrude downward from the separator 12, and the protruding positive electrode plate 10 and / or negative electrode plate 11 are bent and then connected to the current collector. However, when the positive electrode plate 10 or the negative electrode plate 11 is bent as described above, the current collector of the positive electrode plate 10 or the negative electrode plate 11 crosses the separator and is positioned close to the electrode of opposite polarity. Therefore, there is a possibility that the positive electrode plate and the negative electrode plate are in electrical contact with each other and cause an internal short circuit. However, as Figure 5 As shown, when the insulating layer 24 covering a portion of the positive active material layer and the uncoated portion is formed, the insulating layer 24 can prevent the positive electrode plate 10 and the negative electrode plate 11 from electrically contacting each other, thereby preventing a short circuit from occurring inside the battery.

[0058] Preferably, the insulating layer 24 may be disposed on at least one surface of the current collector of the positive electrode plate 10 , and preferably may be disposed on each of both surfaces of the positive electrode plate 10 .

[0059] In addition, the insulating layer 24 may be formed in an area of ​​the positive electrode plate 10 that is likely to face the active material layer 21a of the negative electrode plate 11. For example, in the surface of the uncoated portion 22c of the positive electrode plate 10 that faces the negative electrode plate 11 after bending, the insulating layer 24 may be formed to extend to the distal end of the uncoated portion 22c. However, for the opposite surface of the surface facing the negative electrode plate 11 after bending, it is desirable that the insulating layer 24 is formed only in a portion of the uncoated portion 22c (e.g., before reaching the bending point of the uncoated portion 22c). This is because when the insulating layer 24 is formed on the entire area of ​​the uncoated portion on the opposite surface of the surface facing the negative electrode plate 11, it is impossible to make electrical contact with the current collector, and thus the uncoated portion cannot be used as an electrode tab.

[0060] Meanwhile, the material or composition of the insulating layer 24 is not particularly limited as long as it can be attached to the positive plate while ensuring insulation performance. For example, the insulating layer may be an insulating coating or an insulating tape, and the insulating coating may include an organic binder and inorganic particles. Here, the organic binder may be, for example, styrene-butadiene rubber (SBR), and the inorganic particles may be alumina, but are not limited thereto.

[0061] Next, each of the components of the electrode assembly of the present invention will be described in detail.

[0062] (1) Positive plate

[0063] The positive electrode plate may have a structure in which a positive electrode active material layer is formed on one surface or both surfaces of a positive electrode current collector having a sheet shape, and the positive electrode active material layer may include a positive electrode active material, a conductive material, and a binder.

[0064] Specifically, the positive electrode slurry is manufactured by dispersing the positive electrode active material, the conductive material and the binder in a solvent such as dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone and water. The positive electrode slurry is coated on one surface or both surfaces of the positive electrode current collector having a sheet shape, and the solvent of the positive electrode slurry is removed by a drying process. Then, the positive electrode plate can be manufactured by a rolling process. At the same time, during the coating of the positive electrode slurry, the positive electrode slurry is not applied to a partial area of ​​the positive electrode current collector (for example, one end of the positive electrode current collector). Thus, a positive electrode plate with an uncoated portion can be manufactured.

[0065] Various positive current collectors used in the art can be used as positive current collectors. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used as positive current collectors. The positive current collector can generally have a thickness of 3 μm to 500 μm, and fine protrusions and depressions can be formed on the surface of the positive current collector to increase the adhesion of the positive active material. The positive current collector can be used in various forms (e.g., films, sheets, foils, nets, porous structures, foams, and non-woven fabrics).

[0066] In the present invention, the positive electrode active material includes a lithium nickel-based oxide having a single particle made of one primary particle and / or a quasi-single particle that is an aggregation of not more than 10 primary particles.

[0067] According to the related art, spherical secondary particles in which tens to hundreds of primary particles are aggregated are generally used as positive electrode active materials for lithium secondary batteries. However, for the positive electrode active material having a secondary particle type in which a large number of primary particles are aggregated as described above, the particles will be broken and the primary particles will fall off during the rolling process while manufacturing the positive electrode. In addition, cracks will be generated inside the particles during charging and discharging. When the particles of the positive electrode active material are broken or cracks inside the particles occur, the contact area with the electrolyte increases. Therefore, the gas generation caused by the side reaction with the electrolyte increases. When the gas generation inside the battery increases, the pressure inside the battery increases. Therefore, there is a risk of battery explosion. In particular, when the volume of the cylindrical battery increases, the amount of active material inside the battery increases due to the increase in volume. Therefore, the amount of gas generation also increases significantly, so there is a higher risk of battery fire and / or explosion.

[0068] On the other hand, a positive electrode active material having a single particle type made of one primary particle and / or a quasi-single particle in which no more than 10 primary particles are aggregated has a higher particle strength than an existing positive electrode active material having a secondary particle type in which tens to hundreds of primary particles are aggregated. Therefore, particle breakage hardly occurs during rolling. In addition, for positive electrode active materials having single particles and / or quasi-single particles, the number of primary particles constituting the particles is small. Therefore, the change during charging and discharging due to the volume expansion and contraction of the primary particles is small, so that the generation of cracks inside the particles is significantly reduced.

[0069] Therefore, when a cathode active material having single particles and / or quasi-single particles is used, the amount of gas generation due to particle breakage and internal crack generation can be significantly reduced, thereby achieving excellent safety even in a large-scale battery.

[0070] At the same time, based on the total weight of the positive electrode active material present in the positive electrode active material layer, the lithium nickel-based oxide having single particles and / or quasi-single particles is present in an amount of 95wt% to 100wt% (preferably 98wt% to 100wt%, more preferably 99wt% to 100wt%, and further preferably 100wt%). When the content of single particles and / or quasi-single particles meets the above range, sufficient safety can be obtained when applied to large cylindrical batteries. When the content of the positive electrode active material in the form of secondary particles exceeds 5wt% of the overall positive electrode active material, the side reaction with the electrolyte increases due to the powder generated from the secondary particles during electrode manufacturing and charging / discharging, and the effect of suppressing gas generation is reduced. Therefore, when applied to large batteries, the stability improvement effect may be reduced.

[0071] Meanwhile, in the single particle and / or quasi-single particle form of the positive electrode active material according to the present invention, D min It may be 1.0 μm or more, 1.1 μm or more, 1.15 μm or more, 1.2 μm or more, 1.25 μm or more, 1.3 μm or more, 1.35 μm or more, 1.4 μm or more, 1.45 μm or more, or 1.5 μm or more. min When the particle size is less than 1.0 μm, the particle may be easily broken due to the increase of the roller gap pressure during the rolling process of the positive electrode plate, and the thermal stability may be deteriorated. Therefore, when applied to a large battery, the thermal stability may not be sufficiently ensured.

[0072] At the same time, in terms of resistance and output characteristics, the D min It can be 3 μm or less, 2.5 μm or less, or 2 μm. minWhen D is too large, the diffusion distance of lithium ions within the particles may increase, resulting in deterioration of resistance and output characteristics. min It can be 1.0 μm to 3 μm, 1.0 μm to 2.5 μm, or 1.3 μm to 2.0 μm. 50 It can be 5 μm or less, 4 μm or less, or 3 μm or less, for example, 0.5 μm to 5 μm, preferably 1 μm to 5 μm, and more preferably 2 μm to 5 μm. In the positive electrode active material having single particles and / or quasi-single particles, the interface between the primary particles inside the particles, which serves as a diffusion path for lithium ions, is small. Therefore, compared with the positive electrode active material having a secondary particle type, the lithium mobility is reduced, thereby increasing the resistance. As the particle size increases, this increase in resistance is more intense. When the resistance increases, the capacity and output characteristics are adversely affected. Therefore, the D of the positive electrode active material powder can be 50 The diameter is controlled to be 5 μm or less to minimize the diffusion distance of lithium ions within the positive electrode active material particles, thereby suppressing an increase in resistance.

[0073] In addition, the D max The thickness of the positive electrode active material may be 12 μm to 17 μm, preferably 12 μm to 16 μm, and more preferably 12 μm to 15 μm. max When this range is satisfied, the resistance and capacity characteristics become more excellent. When aggregation occurs between single particles, the D max When the positive electrode active material powder D max When it is too large, the lithium movement path inside the particle becomes longer and the lithium mobility decreases, which may increase the resistance. At the same time, when excessive crushing occurs, the D max When the positive electrode active material powder D max When too small, the electrode density of the positive electrode decreases, and the energy density may deteriorate.

[0074] Meanwhile, the particle size distribution (PSD) of the positive electrode active material is represented by the following equation 1, and may have a value of 3 or less, preferably a value of 2 to 3, and more preferably a value of 2.3 to 3:

[0075] Particle size distribution (PSD) = (D max –D min ) / D 50 [Equation 1].

[0076] When the positive electrode active material has the above-described particle size distribution, it is possible to appropriately maintain the electrode density of the positive electrode and effectively suppress breakage of particles and increase in resistance.

[0077] In the positive electrode active material, the average particle size of the primary particles may be 5 μm or less, 4 μm or less, 3 μm or less or 2 μm or less, for example, 0.5 μm to 5 μm, preferably 1 μm to 5 μm, or more preferably 2 μm to 5 μm. When the average particle size of the primary particles meets this range, a positive electrode active material having single particles and / or quasi-single particles exhibiting excellent electrochemical properties can be formed. When the average diameter size of the primary particles is very small, the number of aggregated primary particles forming the positive electrode active material becomes larger, and the effect of suppressing the generation of particle rupture during rolling is reduced. When the average particle size of the primary particles is very large, the lithium diffusion path inside the primary particles becomes longer, the resistance may increase, and the output characteristics may deteriorate.

[0078] In the present invention, the positive electrode active material preferably contained in the positive electrode active material layer has a unimodal particle size distribution. According to the related art, bimodal positive electrode active materials have been widely used to increase the electrode density of the positive electrode active material layer. A large-particle positive electrode active material having a large average particle size and a small-particle positive electrode active material having a small average particle size are mixed and used in a bimodal positive electrode active material. However, for positive electrode active materials having single particles and / or quasi-single particles, when the particle size increases, the lithium movement path becomes longer, and thus the resistance increases significantly. Therefore, when particles having a large particle size are mixed and used, the capacity and output characteristics may be reduced. Therefore, a positive electrode active material having a unimodal distribution is used in the present invention, so that the increase in resistance can be minimized.

[0079] Meanwhile, the positive electrode active material may include a lithium nickel-based oxide, and specifically may include a lithium nickel-based oxide containing 80 mol% or more of Ni based on the total molar number of transition metals. Preferably, the lithium nickel-based oxide may include 80 mol% or more and less than 100 mol%, 82 mol% or more and less than 100 mol%, or 83 mol% or more and less than 100 mol% of Ni. When a lithium nickel-based oxide containing a high Ni content is used as described above, a high capacity can be achieved.

[0080] More specifically, the lithium nickel-based oxide may have a composition represented by the following Chemical Formula 1:

[0081] [Chemical formula 1]

[0082] Li a Ni b Co c M 1 d M 2 e O2

[0083] In Chemical Formula 1, M 1It can be Mn, Al, or a combination thereof, and is preferably Mn or Mn and Al.

[0084] M 2 can be one or more selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta, and Nb, preferably one or more selected from the group consisting of Zr, Y, Mg, and Ti, and more preferably Zr, Y, or a combination thereof. It is not necessary to contain the M 2 element, but when an appropriate amount of the M 2 element is contained, the M 2 element can be used to promote grain growth during firing or improve the stability of the crystal structure.

[0085] a represents the molar fraction of lithium in the lithium nickel-based oxide, and it can satisfy 0.8 ≤ a ≤ 1.2, 0.85 ≤ a ≤ 1.15, or 0.9 ≤ a ≤ 1.2. When the molar fraction of lithium satisfies this range, the crystal structure of the lithium nickel-based oxide can be formed stably.

[0086] b represents the molar fraction of nickel among all metals other than nickel in the lithium nickel-based oxide, and it can satisfy 0.8 ≤ b < 1, 0.82 ≤ b < 1, 0.83 ≤ b < 1, 0.85 ≤ b < 1, 0.88 ≤ b < 1, or 0.90 ≤ b < 1. When the molar fraction of nickel satisfies this range, a high energy density is presented, and a high capacity can be achieved.

[0087] c represents the molar fraction of cobalt among all metals other than nickel in the lithium nickel-based oxide, and it can satisfy 0 < c < 0.2, 0 < c < 0.18, 0.01 ≤ c ≤ 0.17, 0.01 ≤ c ≤ 0.15, 0.01 ≤ c ≤ 0.12, or 0.01 ≤ c ≤ 0.10. When the molar fraction of cobalt satisfies this range, good resistance characteristics and output characteristics can be achieved.

[0088] d represents the molar fraction of the M 1 element among all metals other than nickel in the lithium nickel-based oxide, and it can satisfy 0 < d < 0.2, 0 < d < 0.18, 0.01 ≤ d ≤ 0.17, 0.01 ≤ d ≤ 0.15, 0.01 ≤ d ≤ 0.12, or 0.01 ≤ d ≤ 0.10. When the molar fraction of the M 1 element satisfies this range, the structural stability of the positive electrode active material is excellent.

[0089] e represents the molar fraction of the M 2 element among all metals other than nickel in the lithium nickel-based oxide, and it can satisfy 0 ≤ e ≤ 0.1 or 0 ≤ e ≤ 0.05.

[0090] Meanwhile, as required, the positive electrode active material according to the present invention may further include a coating layer on the surface of the lithium nickel-based oxide particles, which includes one or more coating elements selected from the group consisting of Al, Ti, W, B, F, P, Mg, Ni, Co, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si and S. Preferably, the coating element may be Al, B, Co or a combination thereof.

[0091] When the coating layer is present on the particle surface of the lithium nickel-based oxide, the contact between the electrolyte and the lithium composite transition metal oxide is suppressed by the coating layer. Therefore, the elution of the transition metal due to a side reaction with the electrolyte or the generation of gas can be reduced.

[0092] The positive electrode active material may be contained in an amount of 80 wt % to 99 wt %, preferably 85 wt % to 99 wt %, and more preferably 90 wt % to 99 wt %, based on the total weight of the positive electrode active material layer.

[0093] Meanwhile, in the present invention, (a) single-walled carbon nanotubes or (b) single-walled carbon nanotubes and bundled carbon nanotubes may be used as the positive electrode conductive material.

[0094] When a positive electrode active material having a single particle and / or a quasi-single particle is used, the maximum distance between the positive electrode active material particles inside the positive electrode active material layer increases to 2 μm or more, specifically 2.5 μm or more, and more specifically 3 μm or more. In one embodiment, the maximum distance does not exceed the size of the quasi-single particle. For example, according to the present invention, the distance between the positive electrode active material particles inside the positive electrode active material layer may be 0.5 μm to 4 μm, and more specifically 0.8 μm to 4 μm. In another embodiment, the distance between the positive electrode active material particles inside the positive electrode active material layer may be 0.5 μm to 5 μm, and more specifically 0.8 μm to 5 μm. When a positive electrode active material having a single particle and / or a quasi-single particle is used as described above, the distance between the positive electrode active material particles becomes larger. Therefore, the contact resistance with the conductive material increases, and the conductivity decreases. Therefore, the content of the conductive material must be increased in order to ensure sufficient conductivity in the electrode to which the positive electrode active material of the single particle and / or quasi-single particle is applied. Specifically, in the case of applying a positive electrode active material having an existing secondary particle type, appropriate conductivity can be achieved when the carbon nanotube content in the positive electrode slurry is about 0.4wt% to 0.6wt%. However, in the case of applying a single-particle and / or quasi-single-particle positive electrode active material, in order to achieve equivalent conductivity, the carbon nanotube content in the positive electrode slurry must be 0.9wt% or more. However, when the carbon nanotube content increases to 0.9wt% or more, aggregation occurs in the positive electrode slurry, the viscosity increases, and the coating performance decreases. Therefore, in order to achieve appropriate coating performance, the viscosity of the positive electrode slurry must be reduced by reducing the solid content. However, when the solid content in the positive electrode slurry decreases, the active material content decreases, and the capacity characteristics decrease.

[0095] In order to solve the above problems, the present invention uses a mixture of single-walled carbon nanotubes and bundled carbon nanotubes as a conductive material. Therefore, the distance between the positive electrode active material particles having a single particle type can be fully covered while minimizing the amount of conductive material to be used, thereby achieving excellent coating processability, capacity characteristics and life characteristics.

[0096] Single-walled carbon nanotubes have a larger specific surface area and a longer average particle size (length) than multi-walled carbon nanotubes. Therefore, when single-walled carbon nanotubes are used, a conductive network can be formed while fully covering the distance between the positive electrode active material particles.

[0097] Specifically, the average particle size of the single-walled carbon nanotubes can be 2 μm to 8 μm, preferably 2.5 μm to 8 μm, and more preferably 3 μm to 7 μm. When the average particle size of the single-walled carbon nanotubes meets this range, the single-walled carbon nanotubes can cover the distance between single particles and / or quasi-single particles, thereby smoothly forming a conductive network.

[0098] In addition, single-walled carbon nanotubes can have a diameter of 500 m 2 / g to 2000m 2 / g (preferably 500m 2 / g to 1800m 2 / g, more preferably 700m 2 / g to 1600m 2 When the specific surface area of ​​the single-walled carbon nanotubes satisfies this range, an excellent effect of improving electrical conductivity can be obtained with only a small amount of the single-walled carbon nanotubes.

[0099] At the same time, based on the total weight of the positive electrode active material layer, the single-walled carbon nanotubes may be present in an amount of 0.001wt% to 0.04wt% (preferably 0.005wt% to 0.03wt%, more preferably 0.01wt% to 0.02wt%). When the single-walled carbon nanotube content exceeds this range, the coating processability may decrease due to the increased viscosity of the positive electrode slurry. In addition, when the solid content in the positive electrode slurry is reduced to achieve appropriate coating performance, the capacity and life characteristics may deteriorate. When the single-walled carbon nanotube content is less than the above range, the conductivity may deteriorate due to insufficient formation of a conductive network, and the life and capacity characteristics may deteriorate due to the conductive network being cut off after cycling. When considering the life and capacity characteristics, it is particularly preferred that the single-walled carbon nanotube content is 0.02wt% or less.

[0100] Meanwhile, the bundled carbon nanotubes refer to carbon nanotubes in which a plurality of carbon nanotube units are arranged in a specific direction to form a secondary shape of a bundle or a rope, and include shapes in which the bundle or rope is twisted or entangled. The bundled carbon nanotubes are different from entangled carbon nanotubes having a shape in which a plurality of carbon nanotubes are entangled without directionality. The average particle size of the bundled carbon nanotubes is smaller than that of the single-walled carbon nanotubes, but larger than that of the entangled carbon nanotubes.

[0101] Specifically, the average particle size of the bundled carbon nanotubes may be 0.5 μm to 5 μm, preferably 0.7 μm to 5 μm, and more preferably 1 μm to 4 μm. 2 / g to 500m 2 / g (preferably 100m 2 / g to 400m 2 / g, more preferably 200m 2 / g to 300m 2 When the average particle size and specific surface area of ​​the bundled carbon nanotubes meet these ranges, a conductive network between the positive electrode active material particles can be fully formed while minimizing the conductive material content, and the viscosity of the positive electrode slurry can be kept low.

[0102] Meanwhile, according to the present invention, the bundled carbon nanotubes may be present in an amount of 0.4 wt% to 0.6 wt% based on the total weight of the positive electrode active material layer. When the bundled carbon nanotube content is less than the above range, the life characteristics decrease rapidly. When the bundled carbon nanotube content exceeds the above range, the viscosity of the positive electrode slurry increases, thereby possibly reducing the coating processability.

[0103] Next, the binder is used to enhance the adhesion between the positive active material particles and the bonding force between the positive active material and the positive current collector. For specific examples, there may be polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM rubber), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers. Any one of them or a mixture of two or more thereof can be used. Based on the total weight of the positive active material layer, the content of the binder can generally be 1wt% to 30wt%, preferably 1wt% to 20wt%, and more preferably 1wt% to 10wt%.

[0104] Meanwhile, an insulating layer may be formed on the positive electrode plate according to the present invention to cover the uncoated portion and a portion of the positive electrode active material layer as required. The insulating layer may be formed in a direction parallel to the winding direction of the electrode assembly.

[0105] (2) Negative plate

[0106] The negative electrode plate may have a structure in which a negative electrode active material layer is formed on one surface or both surfaces of a negative electrode current collector having a sheet shape, and the negative electrode active material layer may include a negative electrode active material, a conductive material, and a binder.

[0107] Specifically, the negative electrode slurry is manufactured by dispersing the negative electrode active material, the conductive material and the binder in a solvent such as dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone and water. The negative electrode slurry is coated on one surface or both surfaces of the negative electrode current collector having a sheet shape, and the solvent of the negative electrode slurry is removed by a drying process. Then, the negative electrode plate can be manufactured by a rolling process. At the same time, during the coating of the negative electrode slurry, the negative electrode slurry is not applied to a partial area of ​​the negative electrode current collector (for example, one end of the negative electrode current collector). Thus, a negative electrode plate with an uncoated portion can be manufactured.

[0108] Compounds capable of reversibly embedding and de-embedding lithium can be used as negative electrode active materials. For specific examples of negative electrode active materials, there may be: carbon-containing materials (e.g., artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon); silicon-based materials (e.g., Si, Si-Me alloy (where Me is one or more selected from the group consisting of Al, Sn, Mg, Cu, Fe, Pb, Zn, Mn, Cr, Ti, and Ni), SiO y (where 0 < y < 2), and Si-C composite materials); lithium metal thin films; and metal materials capable of forming an alloy with lithium (e.g., Sn and Al). Any one or a mixture of two or more of them can be used.

[0109] Preferably, the negative electrode plate according to the present invention may include a silicon-based negative electrode active material. The silicon-based negative electrode active material can be Si, Si-Me alloy (where Me is one or more selected from the group consisting of Al, Sn, Mg, Cu, Fe, Pb, Zn, Mn, Cr, Ti, and Ni), SiO y (where 0 < y < 2), Si-C composite materials or a combination thereof, preferably SiO y (where 0 < y < 2). The silicon-based negative electrode active material has a high theoretical capacity. Therefore, when the silicon-based negative electrode active material is included, the capacity characteristics can be enhanced.

[0110] At the same time, the silicon-based negative electrode active material can be doped with M b metal. Here, the M b metal can be a Group 1 metal element or a Group 2 metal element. Specifically, it can be Li, Mg, etc. Specifically, the silicon negative electrode active material can be Si, SiO b doped with M y (where 0 < y < 2), Si-C composite materials, etc. Regarding the silicon-based negative electrode active material doped with metal, the capacity of the active material is slightly reduced due to the doping element, but the efficiency becomes higher. Therefore, a high energy density can be achieved.

[0111] In addition, the silicon-based negative electrode active material may further include a carbon coating on the particle surface. Here, based on the total weight of the silicon-based negative electrode active material, the amount of the carbon coating can be 20 wt% or less, preferably 1 wt% to 20 wt%.

[0112] In addition, as needed, the negative electrode plate may further include a carbon-based negative electrode active material as the negative electrode active material. The carbon-based negative electrode active material can be, for example, artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon, soft carbon, hard carbon, etc., but is not limited thereto.

[0113] At the same time, when a mixture of a silicon-based negative electrode active material and a carbon-based negative electrode active material is used as a negative electrode active material, the mixing ratio between the silicon-based negative electrode active material and the carbon-based negative electrode active material can be 1:99 to 20:80 by weight, preferably 1:99 to 15:85, and more preferably 1:99 to 10:90.

[0114] The negative electrode active material may be contained in an amount of 80 wt % to 99 wt %, preferably 85 wt % to 99 wt %, and more preferably 90 wt % to 99 wt %, based on the total weight of the negative electrode active material layer.

[0115] At the same time, the negative electrode current collector commonly used in the art can be used as the negative electrode current collector. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium or silver, aluminum-cadmium alloy, etc. can be used. The negative electrode current collector can generally have a thickness of 3 μm to 500 μm, and similar to the positive electrode current collector, fine protrusions and depressions can be formed on the surface of the current collector to enhance the adhesion of the negative electrode active material. For example, various forms such as films, sheets, foils, nets, porous structures, foams and non-woven fabrics can be used.

[0116] The conductive material is used to impart conductivity to the negative electrode, and is not particularly limited as long as it has electronic conductivity without causing chemical changes in the battery to be constructed. For specific examples, there may be: graphite (e.g., natural graphite and artificial graphite); carbon-based materials (e.g., carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber and carbon nanotubes); metal powder or metal fiber (e.g., copper, nickel, aluminum and silver); conductive whiskers (e.g., zinc oxide and potassium titanate); conductive metal oxides (e.g., titanium oxide); or conductive polymers (e.g., polyphenylene derivatives). Any one of them or a mixture of two or more thereof can be used. Based on the total weight of the negative electrode active material layer, the content of the conductive material can generally be 1wt% to 30wt%, preferably 1wt% to 20wt%, and more preferably 1wt% to 10wt%.

[0117] The binder is used to enhance the adhesion between the particles of the negative electrode active material and the adhesion between the negative electrode active material and the negative electrode current collector. For specific examples, there may be: polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP copolymer), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM rubber), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers. Any one of them or a mixture of two or more thereof can be used. Based on the total weight of the negative electrode active material layer, the content of the binder can generally be 1wt% to 30wt%, preferably 1wt% to 20wt%, and more preferably 1wt% to 10wt%.

[0118] (3) Diaphragm

[0119] The separator separates the negative electrode and the positive electrode, and provides a mobile channel for lithium ions, and it is not particularly limited, as long as it is generally used as a separator in a lithium secondary battery. Specifically, a porous polymer film (for example, a porous polymer film prepared from a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer) can be used as a separator, or a laminated structure with two or more layers can be used. In addition, conventional porous nonwoven fabrics (for example, nonwoven fabrics made of glass fibers, polyethylene terephthalate fibers, etc. with a high melting point) can be used as separators. In addition, in order to ensure heat resistance or mechanical strength, a coated separator including a ceramic component or a polymer material can be used.

[0120] Lithium secondary battery

[0121] Next, a lithium secondary battery according to the present invention will be described.

[0122] A battery according to the present invention may include: an electrode assembly having a cake roll type structure in which a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate are wound in one direction; a battery can in which the electrode assembly is accommodated; and a sealing body that seals an open end of the battery can.

[0123] Preferably, the lithium secondary battery according to the present invention may be a cylindrical battery, more preferably a large cylindrical battery having a shape factor ratio (a value obtained by dividing the diameter of a cylindrical battery by the height, i.e., defined as the ratio of the diameter ф to the height H) of 0.4 or more. Here, the shape factor refers to a value indicating the diameter and height of a cylindrical battery.

[0124] The cylindrical battery according to the present invention can be, for example, a 46110 cell (46 mm in diameter, 110 mm in height, and a shape factor ratio of 0.418), a 4875 cell (48 mm in diameter, 75 mm in height, and a shape factor ratio of 0.640), a 48110 cell (48 mm in diameter, 110 mm in height, and a shape factor ratio of 0.436), a 4880 cell (48 mm in diameter, 80 mm in height, and a shape factor ratio of 0.600), and a 4680 cell (46 mm in diameter, 80 mm in height, and a shape factor ratio of 0.575). In the numerical value representing the shape factor, the first two digits represent the diameter of the cell, and the next two or three digits represent the height of the cell.

[0125] In the lithium secondary battery according to the present invention, a positive electrode active material having a single particle and / or a quasi-single particle is applied, so the amount of gas generated is significantly reduced compared with the related art. Therefore, even in a large cylindrical battery having a shape factor ratio of 0.4 or more, excellent safety can be achieved.

[0126] Meanwhile, the battery according to the present invention may preferably be a battery having a jointless structure not including an electrode joint, but is not limited thereto.

[0127] A battery having a jointless structure may have, for example, a structure in which each of the positive electrode plate and the negative electrode plate includes an uncoated portion where an active material layer is not formed. The positive electrode plate uncoated portion and the negative electrode plate uncoated portion are located at the upper end and the lower end of the electrode assembly, respectively. A current collecting plate is coupled to each of the positive electrode plate uncoated portion and the negative electrode plate uncoated portion. The current collecting plate is connected to the electrode terminal.

[0128] Figure 3 A cross-sectional view of a battery having a jointless structure according to an embodiment of the present invention is shown. Figure 3 A battery according to an embodiment of the present invention is described. However, Figure 3 Only one embodiment of the present invention is shown, and the structure of the battery of the present invention is not limited to Figure 3 range shown.

[0129] The battery 140 according to the embodiment of the present invention includes the electrode assembly 141 having the above-described roll cake type, a battery can 142 accommodating the electrode assembly 141 therein, and a sealing body 143 sealing an open end of the battery can 142 .

[0130] Here, each of the positive electrode plate and the negative electrode plate of the electrode assembly may include an uncoated portion where an active material layer is not formed, and may be stacked and wound so that the positive electrode plate uncoated portion and the negative electrode plate uncoated portion are located at the upper end and the lower end of the electrode assembly, respectively. The electrode assembly has been described above, so hereinafter, only other components except the electrode assembly will be described.

[0131] The battery can 142 is a container having an opening formed at an upper side and is made of a conductive metal material such as aluminum or steel. The battery can accommodate the electrode assembly 141 in an inner space through the upper opening and also accommodate an electrolyte together.

[0132] As the electrolyte used in the present invention, various electrolytes that can be used for lithium secondary batteries, such as organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes or molten inorganic electrolytes can be used, however, the type thereof is not particularly limited.

[0133] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0134] The organic solvent is not particularly limited as long as it can act as a medium in which ions participating in the electrochemical reaction of the battery migrate. Specifically, ester-based solvents (e.g., methyl acetate, ethyl acetate, γ-butyrolactone or ε-caprolactone); ether-based solvents (e.g., dibutyl ether or tetrahydrofuran); ketone-based solvents (e.g., cyclohexanone); aromatic hydrocarbon-based solvents (e.g., benzene or fluorobenzene); carbonate-based solvents (e.g., dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), methyl ethyl carbonate (EMC), ethylene carbonate (EC) or propylene carbonate (PC)); alcohol-based solvents (e.g., ethanol, isopropanol); nitrile (e.g., R-CN (wherein R is a linear, branched or cyclic C2-C20 hydrocarbon group, and may include a double bond, an aromatic ring or an ether bond)); amides (e.g., dimethylformamide); dioxolanes (e.g., 1,3-dioxolanes); or cyclopentane sulfone can be used as organic solvents. Among them, carbonate-based solvents are preferably used. More preferably, a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) and a low-viscosity linear carbonate-based compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is used, wherein the cyclic carbonate has high ionic conductivity and high dielectric constant to improve the charge / discharge performance of the battery.

[0135] Lithium salts are not particularly limited as long as they are compounds that can provide lithium ions used in lithium secondary batteries. Specifically, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc. can be used as lithium salts. Lithium salts can be used in a concentration in the range of 0.1M to 5.0M, preferably 0.1M to 3.0M. When the concentration of the lithium salt falls within this range, the electrolyte has appropriate conductivity and viscosity. Therefore, excellent electrolyte performance can be achieved, and lithium ions can be effectively migrated.

[0136] In addition to these electrolyte components, the electrolyte may also include additives for the purpose of improving the life characteristics of the battery, suppressing the reduction of the battery capacity and improving the discharge capacity of the battery. For example, compounds based on halogenated-alkylene carbonates such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, N-glyme dimethyl ether, hexamethylphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N, N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol, aluminum chloride, etc. can be used as additives, and any one of them or a mixture thereof can be used. However, the additive is not limited thereto. Based on the gross weight of the electrolyte, the content of the additive may be 0.1wt% to 10wt%, preferably 0.1wt% to 5wt%.

[0137] The battery can 142 is electrically connected to the non-coating portion 146 b of the negative electrode plate, and contacts the external power source and functions as a negative electrode plate terminal that transmits current that has been applied from the external power source to the negative electrode plate.

[0138] As needed, a curling portion 147 and a crimping portion 148 may be provided at the upper end of the battery can 142. The curling portion 147 may be formed by pressing the periphery of the outer peripheral surface of the battery can 142 to a distance D1. The curling portion 147 prevents the electrode assembly 141 accommodated inside the battery can 142 from escaping through the upper opening of the battery can 142, and may serve as a support member on which the sealing body 143 is placed.

[0139] The crimping portion 148 may be formed above the beading portion 147 and have a shape extending and bending to surround a portion of the outer circumferential surface of the cap plate 143 a disposed above the beading portion 147 and a portion of the top surface of the cap plate 143 a .

[0140] Next, the sealing body 143 is used to seal the open end of the sealed battery can 142, and includes a cover plate 143a and a first gasket 143b that provides airtightness and insulation properties for the space between the cover plate 143a and the battery can 142, and the sealing body 143 may also include a connecting plate 143c that is electrically and mechanically connected to the cover plate 143a as needed. The cover plate 143a may be pressed against a curling portion 147 formed in the battery can 142 and fixed by a crimping portion 148.

[0141] The cap plate 143a is a component made of a metal material having electrical conductivity, and covers the upper opening of the battery can 142. The cap plate 143a is electrically connected to the positive plate of the electrode assembly 141, and is electrically insulated from the battery can 142 by the first gasket 143b. Therefore, the cap plate 143a can be used as a positive terminal of the secondary battery. The cap plate 143a may include a protrusion 143d protruding upward from the winding center C. The protrusion 143d contacts an external power source and allows current to be applied from the external power source.

[0142] The first gasket 143 b may be interposed between the cap plate 143 a and the crimping portion 148 to ensure airtightness of the battery can 142 and electrical insulation between the battery can 142 and the cap plate 143 a .

[0143] Meanwhile, as needed, the battery 140 according to the present invention may further include current collecting plates 144 and 145. The current collecting plates are coupled to the positive plate uncoated portion 146a and the negative plate uncoated portion 146b and connected to electrode terminals (ie, positive and negative terminals).

[0144] Specifically, the battery 140 according to the present invention may include a first current collecting plate 144 coupled to an upper portion of the electrode assembly 141 and a second current collecting plate 145 coupled to a lower portion of the electrode assembly 141 .

[0145] A first current collecting plate 144 and / or a second current collecting plate 145 may also be included.

[0146] The first current collecting plate 144 is coupled to the upper portion of the electrode assembly 141. The first current collecting plate 144 may be made of a conductive metal material such as aluminum, copper or nickel, and is electrically connected to the uncoated portion 146a of the positive electrode plate. A lead 149 may be connected to the first current collecting plate 144. The lead 149 extends upward from the electrode assembly 141 and may be coupled to the connecting plate 143c or directly to the bottom surface of the cap plate 143a. The coupling between the lead 149 and other components may be achieved by welding. Preferably, the first current collecting plate 144 may be integrally formed with the lead 149. In this case, the lead 149 may have a long plate shape extending outward from the central portion of the first current collecting plate 144.

[0147] At the same time, the first current collecting plate 144 is coupled to the end of the non-coating portion 146a of the positive electrode plate. This coupling may be achieved by laser welding, resistance welding, ultrasonic welding, brazing, or the like.

[0148] The second current collecting plate 145 is coupled to the lower portion of the electrode assembly 141. The second current collecting plate 145 may be made of a conductive metal material such as aluminum, copper, or nickel, and is electrically connected to the uncoated portion 146b of the negative electrode plate. One surface of the second current collecting plate 145 may be coupled to the uncoated portion 146b of the negative electrode plate, and the other surface may be coupled to the inner bottom surface of the battery can 142. Here, such coupling may be achieved by laser welding, resistance welding, ultrasonic welding, brazing, or the like.

[0149] Meanwhile, as needed, the battery 140 according to the present invention may further include an insulator 146. The insulator 146 may be provided to cover the top surface of the first current collecting plate 144. The insulator 146 covers the first current collecting plate 144, thereby preventing the first current collecting plate 144 and the battery can 142 from directly contacting each other.

[0150] The insulator 146 includes a lead hole 151 through which the lead 149 extending upward from the first current collecting plate 144 may be led out. The lead 149 is led out upward through the lead hole 151 and coupled to the bottom surface of the connection plate 143c or the bottom surface of the cap plate 143a.

[0151] The insulator 146 may be made of a polymer resin having insulating properties (for example, a polymer resin material such as polyethylene, polypropylene, polyimide, or polybutylene terephthalate).

[0152] At the same time, as needed, the battery 140 according to the present invention may further include a vent 152 formed in the bottom surface of the battery can 142. The vent 152 corresponds to an area of ​​the bottom surface of the battery can 142 having a smaller thickness than the peripheral area. The vent 152 has a smaller thickness and is therefore structurally weaker than the peripheral area. Therefore, when the pressure in the battery 140 rises to a certain level or higher, the vent 152 ruptures and the gas in the battery can 142 is discharged to the outside, thereby preventing the battery from exploding.

[0153] Figure 4 A cross-sectional view of a battery having a jointless structure according to another embodiment of the present invention is shown. Figure 4 A battery according to another embodiment of the present invention is described. However, Figure 4 Only one embodiment of the present invention is shown, and the structure of the battery of the present invention is not limited to Figure 4 range shown.

[0154] Reference Figure 4 ,and Figure 3 Compared to the illustrated battery 140 , a battery 170 according to another embodiment of the present invention is different in the structures of a battery can and a sealing body, but configurations of an electrode assembly and an electrolyte are substantially identical to each other.

[0155] Specifically, the battery 170 includes a battery can 171, and a riveted terminal 172 passes through the battery can 171 and is installed. The riveted terminal 172 is installed on a partially closed surface (upper surface in the figure) of the battery can 171, and the battery can 171 is partially closed at one of its distal ends. The riveted terminal 172 is riveted in the through hole of the battery can 171 in a state where a second gasket 173 having insulating properties is inserted between the riveted terminal 172 and the through hole of the battery can 171 (the first opening at the first distal end). The riveted terminal 172 is exposed outward in a direction opposite to the direction of gravity.

[0156] The riveted terminal 172 includes a terminal exposure portion 172a and a terminal insertion portion 172b. The terminal exposure portion 172a is exposed outward from the partially enclosed surface of the battery can 171. The terminal exposure portion 172a may be located in the approximate central portion of the partially enclosed surface of the battery can 171. The maximum diameter of the terminal exposure portion 172a may be formed to be larger than the maximum diameter of the through hole formed in the battery can 171. The terminal insertion portion 172b passes through the approximate central portion of the partially enclosed surface of the battery can 171 and may be electrically connected to the uncoated portion 146a of the positive plate. The terminal insertion portion 172b may be riveted to the inner surface of the battery can 171. That is, the terminal insertion portion 172b may have a shape that is bent toward the inner surface of the battery can 171. The maximum diameter of the end of the terminal insertion portion 172b may be larger than the maximum diameter of the through hole of the battery can 171.

[0157] The lower end surface of the terminal insertion portion 172b may be welded to the first current collecting plate 144 connected to the uncoated portion 146a of the positive electrode plate. An insulating cover 174 made of an insulating material may be interposed between the first current collecting plate 144 and the inner surface of the battery can 171. The insulating cover 174 covers the upper portion of the first current collecting plate 144 and the upper end edge portion of the electrode assembly 141. Therefore, a short circuit that occurs when the uncoated portion on the periphery of the electrode assembly 141 contacts the inner surface of the battery can 171 having different polarities may be prevented. The terminal insertion portion 172b of the riveted terminal 172 passes through the insulating cover 174 and may be welded to the first current collecting plate 144.

[0158] The second gasket 173 is interposed between the battery can 171 and the rivet terminal 172 and prevents electrical contact between the battery can 171 and the rivet terminal 172 having different polarities. Therefore, the top surface of the rivet terminal 172 having a substantially flat shape can be used as a positive terminal of the battery 170.

[0159] The second gasket 173 includes a gasket exposure portion 173a and a gasket insertion portion 173b. The gasket exposure portion 173a is inserted between the terminal exposure portion 172a of the riveted terminal 172 and the battery can 171. The gasket insertion portion 173b is inserted between the terminal insertion portion 172b of the riveted terminal 172 and the battery can 171. When the terminal insertion portion 172b is riveted, the gasket insertion portion 173b can be deformed together and in close contact with the inner surface of the battery can 171. The second gasket 173 can be made of, for example, a polymer resin having insulating properties.

[0160] The gasket exposed portion 173a of the second gasket 173 may have a shape extending to cover the outer peripheral surface of the terminal exposed portion 172a of the riveted terminal 172. When the second gasket 173 covers the outer peripheral surface of the riveted terminal 172, a short circuit may be prevented from occurring during a process of coupling an electrical connection component such as a bus bar to the riveted terminal 172 and / or the top surface of the battery can 171. Although not shown, the gasket exposed portion 173a may have a shape extending to cover a portion of the top surface of the terminal exposed portion 172a as well as the outer peripheral surface thereof.

[0161] When the second gasket 173 may be made of a polymer resin, the second gasket 173 may be coupled to the battery can 171 and the riveted terminal 172 by thermal fusion. In this case, airtightness may be enhanced at a coupling interface between the second gasket 173 and the riveted terminal 172 and a coupling interface between the second gasket 173 and the battery can 171. Meanwhile, when the gasket exposed portion 173a of the second gasket 173 has a shape extending to the top surface of the terminal exposed portion 172a, the riveted terminal 172 may be integrally coupled to the second gasket 173 by insert injection molding.

[0162] The remaining area 175 on the top surface of the battery can 171 excluding the area occupied by the rivet terminal 172 and the second gasket 173 corresponds to a negative terminal having a polarity opposite to that of the rivet terminal 172 .

[0163] The second current collecting plate 176 is coupled to the lower portion of the electrode assembly 141. The second current collecting plate 176 may be made of a conductive metal material such as aluminum, steel, copper, or nickel, and is electrically connected to the non-coating portion 146b of the negative electrode plate.

[0164] Preferably, the second current collecting plate 176 is electrically connected to the battery can 171. To this end, at least a portion of the edge portion of the second current collecting plate 176 may be inserted and fixed between the inner surface of the battery can 171 and the first gasket 178b. In one example, at least a portion of the edge portion of the second current collecting plate 176 may be fixed to the curling portion 180 formed at the lower end of the battery can 171 by welding, while being supported by the lower end surface of the curling portion 180. In a modified example, at least a portion of the edge portion of the second current collecting plate 176 may be directly welded to the inner wall surface of the battery can 171.

[0165] The second current collecting plate 176 may include a plurality of protrusions and recesses radially formed on a surface facing the non-coating portion 146 b. When the protrusions and recesses are formed, the protrusions and recesses may be press-fitted into the non-coating portion 146 b by pressing the second current collecting plate 176 .

[0166] Preferably, the second current collecting plate 176 and the end of the non-coating portion 146 b may be coupled by welding (eg, laser welding).

[0167] The sealing body 178 for sealing the lower open end of the battery can 171 includes a cover plate 178a and a first gasket 178b. The first gasket 178b electrically separates the cover plate 178a from the battery can 171. The crimping portion 181 fixes the edge of the cover plate 178a and the first gasket 178b together. The exhaust portion 179 is provided in the cover plate 178a. The exhaust portion 179 has substantially the same configuration as the above-mentioned embodiment.

[0168] Preferably, the cover plate 178a may be made of a conductive metal material. However, since the first gasket 178b is interposed between the cover plate 178a and the battery can 171, the cover plate 178a has no electrical polarity. The seal 178 is used to seal the lower open end of the battery can 171 and discharge gas when the internal pressure of the battery 170 rises to a threshold value or higher.

[0169] Preferably, the riveted terminal 172 electrically connected to the uncoated portion 146a of the positive plate is used as a positive terminal. In addition, a portion 175 other than the riveted terminal 172 on the upper surface of the battery can 171 electrically connected to the uncoated portion 146b of the negative plate through the second current collector 176 is used as a negative terminal. As described above, when the two electrode terminals are located at the upper part of the battery, an electrical connection component such as a bus bar can be provided only on one side of the battery 170. This can lead to simplification of the battery pack structure and improvement of energy density. In addition, the portion 175 used as the negative terminal has a substantially flat shape, so that when an electrical connection component such as a bus bar is joined, a sufficient joining area can be ensured. Therefore, in the battery 170, the resistance at the joining portion for the electrical connection component can be reduced to a preferred level.

[0170] When the lithium secondary battery is formed into the above-mentioned jointless structure, current concentration becomes smaller than that of the battery with electrode joints in the related art, and thus, the heat generation inside the battery can be effectively reduced. Therefore, the improvement of the thermal stability of the battery can be obtained.

[0171] The lithium secondary battery according to the present invention as described above may be used to manufacture a battery pack. Figure 6 The configuration of a battery pack according to an embodiment of the present invention is schematically shown. Figure 6 , a battery pack 3 according to an embodiment of the present invention includes: an assembly in which a secondary battery 1 is electrically connected; and a battery pack case 2 accommodating the assembly. The secondary battery 1 is a battery cell according to the above-mentioned embodiment. In the figure, for the convenience of illustration, components such as a bus bar for electrically connecting the secondary battery 1, a cooling unit, and an external terminal are omitted.

[0172] The battery pack 3 can be mounted on a vehicle. The vehicle can be, for example, an electric vehicle, a hybrid vehicle, or a plug-in hybrid vehicle. The vehicle includes a four-wheel vehicle or a two-wheel vehicle.

[0173] Figure 7 It is used to describe Figure 6 3. A view of a vehicle with a battery pack.

[0174] Reference Figure 7 , the vehicle 5 according to the embodiment of the present invention includes the battery pack 3 according to the embodiment of the present invention, and runs by receiving electric power from the battery pack 3 .

[0175] Hereinafter, the present invention will be described in more detail with reference to specific embodiments.

[0176] Implementation Method 1

[0177] The positive electrode active material, single-walled CNT, bundled CNT and PVDF binder were mixed in N-methylpyrrolidone at a weight ratio of 97.42:0.01:0.6:1.97, thereby manufacturing a positive electrode slurry.

[0178] Here, 100% Li[Ni 0.93 Co 0.05 Mn 0.01 Al 0.01 ]O2 was used as the positive electrode active material, which had a D min , D of 4.23 μm 50 and D of 13.1 μm max , and in which single particles and quasi-single particles are mixed.

[0179] PD-0521 manufactured by OSCiAL was used as the single-walled CNT, and its average particle size was 5.0 μm.

[0180] BT1001M-K5 manufactured by LG Chem Co., Ltd. was used as the bundled CNT, and the average particle size thereof was 3.0 μm.

[0181] The positive electrode slurry was coated on one surface of an aluminum current collector sheet, dried at 120° C., and then rolled, thereby manufacturing a positive electrode plate.

[0182] The negative electrode active material (graphite), the conductive material (Super C), styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) were mixed in water at a weight ratio of 98.05:0.05:1.0:0.9. Thus, a negative electrode slurry was manufactured. The negative electrode slurry was coated on one surface of a copper current collector sheet, dried at 150°C, and then rolled. Thus, a negative electrode plate was manufactured.

[0183] The separator is inserted between the positive plate and the negative plate manufactured as described above, and then the separator / positive plate / separator / negative plate are stacked in this order, and then wound. Thus, an electrode assembly having a cake roll type is manufactured. The electrode assembly manufactured as described above is inserted into a cylindrical battery can, and then the electrolyte is injected therein. Thus, a 4680 battery cell is manufactured.

[0184] Implementation Method 2

[0185] The 4680 battery cell was manufactured by the same method as in Embodiment 1, except that when the positive electrode slurry was manufactured, the positive electrode active material, single-walled CNT, bundled CNT, and PVDF binder were mixed in a weight ratio of 97.41:0.02:0.6:1.97.

[0186] Implementation 3

[0187] The 4680 battery cell was manufactured by the same method as in Embodiment 1, except that when manufacturing the positive electrode slurry, the positive electrode active material, the single-walled carbon nanotubes, the bundled carbon nanotubes, and the PVDF binder were mixed in a weight ratio of 97.40:0.03:0.6:1.97.

[0188] Implementation 4

[0189] The 4680 battery cell was manufactured by the same method as in Embodiment 1, except that when manufacturing the positive electrode slurry, the positive electrode active material, the single-walled carbon nanotubes, the bundled carbon nanotubes, and the PVDF binder were mixed in a weight ratio of 97.39:0.04:0.6:1.97.

[0190] Implementation method 5

[0191] A 4680 battery cell was manufactured by the same method as in Embodiment 1, except that when manufacturing the positive electrode slurry, the positive electrode active material, the single-walled carbon nanotubes, the bundled carbon nanotubes, and the PVDF binder were mixed in a weight ratio of 97.52:0.01:0.5:1.97.

[0192] Implementation 6

[0193] The 4680 battery cell was manufactured by the same method as in Embodiment 1, except that when the positive electrode slurry was manufactured, the positive electrode active material, single-walled CNT, bundled CNT, and PVDF binder were mixed in a weight ratio of 97.61:0.02:0.4:1.97.

[0194] Implementation 7

[0195] The 4680 battery cell was manufactured by the same method as in Embodiment 1, except that when manufacturing the positive electrode slurry, the positive electrode active material, the single-walled CNT, the bundled CNT, and the PVDF binder were mixed in a weight ratio of 97.625:0.005:0.4:1.97.

[0196] Comparative Example 1

[0197] The 4680 battery cell was manufactured by the same method as in Embodiment 1, except that when manufacturing the positive electrode slurry, the positive electrode active material, bundled CNTs, and PVDF binder were mixed in a weight ratio of 97.63:0.4:1.97 without using single-walled carbon nanotubes.

[0198] Comparative Example 2

[0199] The 4680 battery cell was manufactured by the same method as in Embodiment 1, except that when manufacturing the positive electrode slurry, the positive electrode active material, bundled CNTs, and PVDF binder were mixed in a weight ratio of 97.43:0.6:1.97 without using single-walled carbon nanotubes.

[0200] Experimental Example 1: Evaluation of Cycle Characteristics

[0201] The 4680 battery cells manufactured by the embodiments and comparative examples were charged to 4.2V at 0.5C constant current-constant voltage at 25°C, and then discharged to 2.5V at 0.5C constant current. This process was defined as one cycle, and charging and discharging were repeated. Then, the capacity retention rate after 100 cycles and the number of cycles when the capacity retention rate reached 90% were measured.

[0202] The measurement results are shown in Table 1 below.

[0203] [Table 1]

[0204]

[0205] As shown in Table 1 above, the lithium secondary batteries of Embodiments 1 to 7 using both single-walled carbon nanotubes and bundled carbon nanotubes as conductive materials exhibited life characteristics superior to those of Comparative Examples 1 and 2 using only bundled carbon nanotubes.

[0206] Experimental Example 2: Examination of the distance between single particles inside the active material layer

[0207] The minimum value (Min.), maximum value (Max.) and average value (Avg.) of the distance between the positive electrode active material particles of the 4680 battery cells manufactured by Embodiment 1 were measured before and after the cycle. Specifically, the positive electrode was separated from the battery cell before the cycle and the battery cell after 100 cycles, and then the positive electrode was cut in the thickness direction by an ion milling device. Subsequently, an image of the cross section of the positive electrode was captured by SEM, and the minimum value (Min.), maximum value (Max.) and average value (Avg.) of the distance between the positive electrode active material particles were measured by an image analysis management system. The measurement results are shown in Table 2 below. In addition, Figure 8 The measurement images after 100 cycles are shown.

[0208] [Table 2]

[0209] Distance between particles (μm) Before executing the loop After 100 cycles Min. 0.8 0.8 Max. 3.0 3.3 Avg. 1.6 1.6

[0210] Through Table 2, Table 3 below and Figure 8 , it can be seen that when a positive electrode active material made of single particles and / or quasi-single particles is used, the maximum value of the distance between the positive electrode active material particles is 3 μm or more. In addition, as charging and discharging proceed, the distance further increases. For example, reviewing the IAM instrument image Figure 8 , different distances were measured at different locations. Table 3 provides a summary of these measurements.

[0211] [Table 3]

[0212] Measurement location Distance(μm) 0 1.31 1 0.91 2 1.77 3 2.96 4 1.98 5 1.83 6 1.75 7 1.15 8 1.03 9 1.15 10 0.71 11 1.35 12 1.23 13 1.03 14 0.62 15 2.82 16 3.69

Claims

1. A lithium secondary battery, comprising: An electrode assembly, in which a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate are wound in one direction; a battery can in which the electrode assembly is accommodated; as well as a sealing body, the sealing body sealing the open end of the battery can, The positive electrode plate comprises a positive electrode active material layer, and the positive electrode active material layer comprises a positive electrode active material, a conductive material and a binder. The positive electrode active material includes a lithium nickel-based oxide having at least one of a single particle type or a quasi-single particle type, and The conductive material includes single-walled carbon nanotubes and bundled carbon nanotubes.

2. The lithium secondary battery according to claim 1, wherein The positive electrode active material layer includes the bundled carbon nanotubes in an amount of 0.4 wt % to 0.6 wt %.

3. The lithium secondary battery according to claim 1, wherein The positive active material layer includes the single-walled carbon nanotube in an amount of 0.001 wt % to 0.04 wt %.

4. The lithium secondary battery according to claim 1, wherein The positive active material layer includes the single-walled carbon nanotube in an amount of 0.01 wt % to 0.02 wt %.

5. The lithium secondary battery according to claim 1, wherein The single-walled carbon nanotubes have an average particle size of 2 μm to 8 μm, and The bundled carbon nanotubes have an average particle size of 0.5 μm to 5 μm.

6. The lithium secondary battery according to claim 1, wherein The maximum distance between particles of the positive electrode active material inside the positive electrode active material layer is 2 μm or more.

7. The lithium secondary battery according to claim 1, wherein: The lithium nickel-based oxide is present in an amount of 95 wt % to 100 wt % based on the total weight of the positive electrode active material present in the positive electrode active material layer.

8. The lithium secondary battery according to claim 1, wherein The positive electrode active material D 50 5μm or less.

9. The lithium secondary battery according to claim 1, wherein: The positive electrode active material D min 1.0 μm or more.

10. The lithium secondary battery according to claim 1, wherein The positive electrode active material D max 12μm to 17μm.

11. The lithium secondary battery according to claim 1, wherein The particle size distribution PSD of the positive electrode active material is represented by the following equation 1 and has a value of 3 or less: Equation 1: Particle size distribution PSD = (D max –D min ) / D 50 .

12. The lithium secondary battery according to claim 1, wherein The positive electrode active material has a unimodal particle size distribution showing a single peak in a volume cumulative particle size distribution graph.

13. The lithium secondary battery according to claim 1, wherein The lithium nickel-based oxide includes 80 mol % or more of Ni based on the total moles of transition metals in the lithium nickel-based oxide.

14. The lithium secondary battery according to claim 1, wherein The lithium nickel-based oxide has a composition represented by the following Chemical Formula 1: Chemical formula 1: Li a Ni b Co c M 1 d M 2 e O2 Among them, in Chemical Formula 1, M 1 is Mn, Al or a combination thereof, and M 2 is Zr, W, Ti, Mg, Ca, Sr, and Ba, 0.8 ≤ a ≤ 1.2, 0.83 ≤ b < 1, 0 < c < 0.17, 0 < d < 0.17, and 0 ≤ e ≤ 0.

1.

15. The lithium secondary battery according to claim 1, wherein The primary particle diameter of the lithium nickel-based oxide is 0.5 μm to 5 μm.

16. The lithium secondary battery according to claim 1, wherein The negative electrode plate includes a silicon-based negative electrode active material.

17. The lithium secondary battery according to claim 1, wherein: The negative electrode plate includes a silicon-based negative electrode active material and a carbon-based negative electrode active material.

18. The lithium secondary battery according to claim 17, wherein: The silicon-based negative electrode active material and the carbon-based negative electrode active material are present in a weight ratio of 1:99 to 20:

80.

19. The lithium secondary battery according to claim 1, wherein: The lithium secondary battery is a cylindrical battery having a shape factor ratio of 0.4 or more.

20. The lithium secondary battery according to claim 19, wherein The cylindrical battery is a 46110 battery cell, a 4875 battery cell, a 48110 battery cell, a 4880 battery cell or a 4680 battery cell.

21. The lithium secondary battery according to claim 1, wherein Each of the positive electrode plate and the negative electrode plate includes an uncoated portion where an active material layer is not formed, Wherein, at least a portion of the uncoated portion of the positive electrode plate or the negative electrode plate defines an electrode tab.

22. The lithium secondary battery according to claim 21, wherein The uncoated portion of the positive electrode plate and the uncoated portion of the negative electrode plate are respectively formed at an end portion of one side of the positive electrode plate and an end portion of one side of the negative electrode plate in a winding direction of the electrode assembly, wherein a current collecting plate is coupled to each of the uncoated portion of the positive electrode plate and the uncoated portion of the negative electrode plate, and The current collecting plate is connected to the electrode terminal.

23. The lithium secondary battery according to claim 22, wherein: Each of the uncoated portion of the positive electrode plate and the uncoated portion of the negative electrode plate is processed into a form of a plurality of segments that can be bent independently, and At least a portion of the plurality of segments is bent toward a winding center of the electrode assembly.

24. The lithium secondary battery according to claim 23, wherein: At least a portion of the plurality of curved segments overlap at an upper end and a lower end of the electrode assembly, and The current collecting plate is coupled to the overlapping plurality of segments.

25. The lithium secondary battery according to claim 21, wherein An insulating layer is further provided on the positive electrode plate in a direction parallel to the winding direction, and the insulating layer covers a portion of the positive electrode active material layer and a portion of the uncoated portion. 26 . A battery pack comprising the lithium secondary battery according to claim 1 .

27. A vehicle comprising the battery pack according to claim 26.

Citation Information

Patent Citations

  • Nitrogen-containing compounds, electronic components and electronic devices

    KR1020220121174A